PERSPEKTIF EKONOMI DAN BISNIS ISLAM ANALISIS STRATEGI TEORI BAURAN PEMASARAN PADA BISNIS KULINER CAFE KOPI TUBING DI KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Kautsar, Hilal Fadillah; Thantawi, Tubagus Rifqy; Fadilah, Hafid (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
The marketing mix is ​​a comprehensive business operating system intended to plan, price, promote, and distribute goods that meet customer needs and achieve company and target market goals. The marketing mix strategy implemented by Cafe Kopi Tubing is product, price, place and promotion. The products are in the form of food and drinks. The prices are quite affordable and have various prices depending on the type of food and drink ordered. The Tubing Coffee Cafe has a beautiful place with a natural feel. The promotion is quite effective using social media such as Instagram, WhatsApp, Facebook and other social media. The marketing mix strategy in sales at Café Kopi Tubing is by maintaining the delicious taste of the food and maintaining the quality of the raw materials for the product itself, using competitive prices with others, a beautiful place, and marketing it quite effectively. This marketing mix strategy has a positive influence on the crowd of customers who visit Café Kopi Tubing. According to the Islamic Economics and Business Perspective, the implementation of the marketing mix for Cafe Kopi Tubing is in accordance with sharia marketing. In terms of food and beverage products, always be honest and prioritize the quality of food and beverage products. In terms of price, the price is in accordance with the quality of food and beverage products. In terms of place, it provides a sense of comfort and a way that is easy for customers to reach. In terms of promotion, we always emphasize ethics in business, don't cheat, don't sell products that are forbidden by Islam, never force customers to buy their products, don't bring down other people's business in marketing their products.